Empowering Digital Philanthropy through the Development of a Social Media Application for Cross-Country Donations at PT. Lasari Kopi - Muh Riyaldi Pratama; Neneng Awaliyah; Taufik Arsandi; Muhammad Irfan Bin Zulkifli; Akbar Hendra; Kamaruddin Kamaruddin (Jurnal Abdimas Cendekiawan Indonesia, 2025)
The rapid advancement of digital technology has changed how people interact and collaborate, positioning social media as a strategic medium for social engagement and humanitarian action. This community service project was conducted at PT. Lasari Kopi Makassar, aims to develop a social-media-based application for cross-country social donations that integrates technology, transparency, and social participation. Using a Research and Development (R&D) approach, the project began with a needs analysis involving interviews and surveys of employees, community partners, and digital volunteers. The data were used to design the application’s main features, including segmented registration, campaign creation, and integration with secure cross-border payment systems. The application was built using the Flutter multiplatform framework to ensure responsive performance across devices. Testing was carried out directly at PT. Lasari Kopi’s Digital Innovation Division served as the pilot site for training and user trials. The results show that the application effectively facilitated donation activities, simplified user access through a login-optional interface, and encouraged social participation through interactive campaign and collaboration features. Participants reported positive experiences regarding usability, security, and transaction flexibility. This program demonstrates the synergy between academia and industry in applying digital innovation to social empowerment. The collaboration with PT. Lasari Kopi illustrates how technology can support corporate social responsibility (CSR) initiatives and strengthen the culture of giving. The developed application has strong potential to become a scalable solution for promoting digital philanthropy and global social solidarity in the modern era.